PENGARUH KARAKTERISTIK PEKERJAAN DAN KEPUASAN KERJA TERHADAP TURNOVER INTENTION PADA TOKO BAZAR MALL LEMBUSWANA SAMARINDA - RIYAN DEVI DAMAYANTI; M. AMIN KADAFI (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2016)
The purpose of this research is to find out examine the effectiveness of the control of trade and analyze the soundness of financial at PT. Pelabuhan Indonesia IV (Persero) branch of Samarinda. The results of this research indicate that PT Pelabuhan Indonesia (Persero) branch of Samarinda has not been effective in managing its receivables in accordance with the standards and deadlines that have been set by the company but by the analysis of financial performance of the financial statements for the period 2012-2015 to assess the health of the financial aspects of the use of five indicators: Return On Investment, Current Ratio, Cash Ratio, Collection Period and total Asset Turn Over. The results showed that the level of health in 2012 received a designation healthy with AAA category and in 2015 received a designation healthy with AA category.Keywords: Control Accounts receivable, financial soundness.